Settlement of the "Cleaning Operation" Case of the Rohingya Ethnic in Myanmar Based on International Law - Santoso, Dimas Bagus; Al Khanif; Arundhati, Gautama Budi (Jurnal Suara Hukum, 2024)
The Independent International Fact-Finding Mission on Myanmar (IIFFMM) released a report on August 27, 2018, documenting over 10,000 deaths and the displacement of more than 725,000 Rohingyas to Bangladesh due to "clearance operations" conducted by the Myanmar Military. These actions constitute severe violations of international human rights law, potentially amounting to crimes against humanity, for which perpetrators could face prosecution at the International Criminal Court (ICC). However, Myanmar's non-ratification of the Rome Statute presents a significant obstacle to effective enforcement. Therefore, a more robust approach is necessary to address the plight of the Rohingya ethnic group affected by these operations. This study adopts a normative research methodology employing both statutory analysis and case study approaches. The Tatmadaw's culpability in committing acts of genocide against the Rohingya ethnic group has been established. To address this, three key mechanisms are proposed: the application of the Responsibility to Protect (R2P) principle, the involvement of international governmental organizations (IGOs), and the pursuit of justice through ICC proceedings. Urgent action is required to ensure accountability for those responsible for genocide, particularly high-ranking Tatmadaw officials, thereby preventing impunity from perpetuating.